Hemoglobin A1c in Patients on Peritoneal Dialysis: How Should We Interpret It?. Issue 5 (25th February 2014) - Coelho, Silvia; Rodrigues, Anabela
Abstract Almost half the patients on peritoneal dialysis are diabetic and glycemic control is essential to improve both patient and technique survival. Hemoglobin A1c (HbA1c) is widely used in the general population for diabetes diagnosis and monitoring as it highly correlates with blood glucose levels and outcomes. Its use has been extrapolated to the peritoneal dialysis population, despite HbA1c being commonly underestimated. In renal failure patients, HbA1c is influenced by variables affecting not only glycemia but also hemoglobin and the time of interaction between the two. Importantly, the impact of these variables differs in peritoneal dialysis compared to non‐dialysis chronic kidney disease and hemodialysis patients. Although HbA1c in peritoneal dialysis patients is less directly associated with blood glucose levels than in the general population, studies have confirmed its association with patient mortality. In this paper we review the variables that can influence HbA1c value emphasizing their impact in peritoneal dialysis patients. By providing clinicians with a comprehensive understanding of HbA1c results, we provide them with tools for a better patient management care and potential improved outcomes of peritoneal dialysis patients.